FLOUTING MAXIM IN EMMA WATSONâ€™S â€œBEING 30 AND HAPPILY SINGLEâ€ BRITISH VOGUE INTERVIEW - Rahayu, Yulia; Kustanti, Dewi; Fauzi, Erfan Muhammad (CALL, 2022)
This study was done to find out more about how a person talks. Conversations between two or more people are usually inseparable from mistakes, uncooperative actions and often exceed expectations. Therefore, an observation in an interview between Paris Lee and Emma Watson is intended to examine the flouting maxim in the speeches made. This research uses qualitative methods with Griceâ€™s supporting theories cooperative principle and flouting maxim. Several data are included in the flouting maxim, namely four data flouting maxim of quantity, three data flouting maxim of quality, four data flouting maxim of manner, and two data flouting maxim relation. From the data analysis, it can be known that the flouting maxim arises when one of the participants, Watson and Paris, insert implied meaning into their speech until they were not cooperative during the interview.Â Keywords: flouting maxim, cooperative principle, utterance, conversation, interview